2009
DOI: 10.1063/1.3257178
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of atomic-scale arsenic clustering in highly doped silicon

Abstract: Low temperature (675 °C) epitaxial in situ doped Si layers (As, 1.5 at. %) were analyzed by atom probe tomography (APT) to study clustering in a highly arsenic-doped silicon layer. The spatial distribution of As atoms in this layer was obtained by APT, and the distance distribution between first nearest neighbors between As atoms was studied. The result shows that the distribution of As atoms is nonhomogeneous, indicating clustering. Those clusters, homogeneously distributed in the volume, are found to be very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…It is believed that increasing As concentration may lead to deactivation of the electrically active arsenic in Si/Ge. Various arsenic–vacancy clusters as well as precipitates (such as monoclinic SiAs and GeAs) were observed that contribute to the deactivation of arsenic in heavily As‐implanted Si/Ge systems . Although we do not address the doping process of As impurities in Si/Ge in this work, studies on the properties of the possible precipitates (silicon and germanium arsenides) are helpful and meaningful in the theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that increasing As concentration may lead to deactivation of the electrically active arsenic in Si/Ge. Various arsenic–vacancy clusters as well as precipitates (such as monoclinic SiAs and GeAs) were observed that contribute to the deactivation of arsenic in heavily As‐implanted Si/Ge systems . Although we do not address the doping process of As impurities in Si/Ge in this work, studies on the properties of the possible precipitates (silicon and germanium arsenides) are helpful and meaningful in the theory.…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic has been used as a doping agent in silicon and germanium to produce n‐type semiconductors for several decades, and many studies have been done on this subject. Even quite recently, the doping issues of As impurities in silicon and germanium are still research topics indicating the importance of the SiAs and GeAs systems . The phase diagrams of the silicon–arsenic and germanium–arsenic systems showed two types of compounds, i.e., XAs and XAs 2 (X = Si, Ge) .…”
Section: Introductionmentioning
confidence: 99%
“…[51][52][53] Nowadays, this technique is increasingly used in different nanoscience domains. [54][55][56][57][58][59][60] Moreover, due to its 3D character, TAP is much more versatile and much more adapted to identify small clusters and to analyze chemical inhomogeneities with respect to conventional HRTEM that gives local informations due to its 2D character.…”
mentioning
confidence: 99%
“…However, in other systems, and outside the spinodal region, dilute and diffuse clusters are observed to form before the equilibrium phase precipitates. Such nonclassical nucleation processes were observed both in metals (Fe-Cu, Fe-Cr) and in semiconductors (Si-B, Si-As) using atom probe tomography (APT) [16,17]. Because of its ultimate spatial resolution, APT has played a major role in the investigation of the early stages of decomposition [18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
mentioning
confidence: 99%